Industrialization process level of Oca Pilot Plant (OCA) - Yenque Dedios, Julio (2008)
This research work is the experimental design of a process for application-level pilot plant in the industrialization of the goose, aimed at developing nectar mix (mixture of goose with tuna) and confit of goose. In experiments development of nectar it has been determined that the mixture of improved organoleptic characteristics in which it made with a 20% Pear. Regarding the confit was used sucrose syrup from 30 to 75 ° Brix concentration being found that the optimum time for each dive is 24 hours.